Community Based Halal Governance: Integrating Living Law, Islamic Values, and Local Institutions in Sustainable Rural Tourism - Mukhlishin Mukhlishin; Siti Aisyah Sabri (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
As tourism activities continue to increase, the absence of clearly institutionalized governance mechanisms creates potential challenges related to coordination, consistency of halal compliance, equitable benefit sharing, and the long term sustainability of community participation. However, these governance dynamics have received very limited scholarly attention. This study aims to examine the gap between formal halal tourism management and the social realities of communities with strong customary and religious traditions by analyzing how mutual cooperation (gotong royong), customary agreements, and Islamic values shape community based halal tourism governance in Mantar Village, West Sumbawa Regency. A qualitative case study approach was employed through in depth interviews with 18 stakeholders, including traditional leaders, religious leaders, tourism actors, village officials, and community members. Data were further enriched through participatory observation and focus group discussions and analyzed using thematic and interpretive techniques within the perspectives of living law and Maqāṣid al Sharī’ah. The findings demonstrate that mutual cooperation serves as the primary operational mechanism for tourism management, while customary agreements function as an effective living legal system regulating social and economic interactions. The integration of customary norms, Islamic principles, and local economic interests enhances governance legitimacy, social cohesion, and the long term sustainability of halal tourism. This study contributes by proposing a Community Based Halal Governance model that strengthens the role of local institutions as a complementary governance framework for sustainable and inclusive halal tourism development in rural destinations.